The Breakthrough Listen Search for Intelligent Life: Target Selection of Nearby Stars and Galaxies. (24th March 2017) - Isaacson, Howard; Siemion, Andrew P. V.; Marcy, Geoffrey W.; Lebofsky, Matt; Price, Danny C.; MacMahon, David; Croft, Steve; DeBoer, David; Hickish, Jack; Werthimer, Dan; Sheikh, Sofia; Hellbourg, Greg; et al.
Abstract: We present the target selection for the Breakthrough Listen search for extraterrestrial intelligence during the first year of observations at the Green Bank Telescope, Parkes Telescope, and Automated Planet Finder. On the way to observing 1, 000, 000 nearby stars in search of technological signals, we present three main sets of objects we plan to observe in addition to a smaller sample of exotica. We chose the 60 nearest stars, all within 5.1 pc from the Sun. Such nearby stars offer the potential to observe faint radio signals from transmitters that have a power similar to those on Earth. We add a list of 1649 stars drawn from the Hipparcos catalog that span the Hertzprung-Russell diagram, including all spectral types along the main sequence, subgiants, and giant stars. This sample offers diversity and inclusion of all stellar types, but with thoughtful limits and due attention to main sequence stars. Our targets also include 123 nearby galaxies composed of a "morphological-type-complete" sample of the nearest spirals, ellipticals, dwarf spherioidals, and irregulars. While their great distances hamper the detection of technological electromagnetic radiation, galaxies offer the opportunity to observe billions of stars simultaneously and to sample the bright end of the technological luminosity function. We will also use the Green Bank and Parkes telescopes to survey the plane and central bulge of the Milky Way. Finally, the complete target list includes several classes of exotica, including white dwarfs, brown dwarfs, black holes, neutron stars, and asteroids in our solar system.